KESADARAN HUKUM MASYARAKAT ATAS PENETAPAN BATAS PENGUASAAN TANAH/RUANG DI WILAYAH PESISIR DAN PANTAI - Yona Yonanda Soly; Yuwono Prianto (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
Indonesia is an archipelagic country, consisting 17,508 big and small islands. People need  for land is increasing in big cities, and also those in small islands. The one and only way for people in small islands meet the need for land is by exploiting coastal areas and beaches to be a place of residence and place of business. Coastal and costal areas should be protected by spatial planning systems and managed wisely by local governments. Any development activities and utilization of coastal areas shall be subject to the provisions of the written positive law. Communities should also understand   that development and community activities can impact on the availability of fish and the presence of coral reefs, mangrove forests or seagrass beds whose existence can affect the livelihoods of local communities. The research method used is empirical. It is necessary to prevent the utilization of coastal border space for purposes other than public purposes. The beach is owned by everyone, therefore it must be prevented exclusive use for personal interest by making a fence or building directly on the beach.Keyword: beach, coastal, small islands